Ecological Geography of the Phytoplankton Associated to Bio-Optical Variability and HPLC-Pigments in the Central Southwestern Gulf of Mexico - Eduardo Millán-Núñez; Martín Efraìn De la Cruz-Orozco (Journal of Marine Science and Engineering)
An oceanographic cruise with 34 stations was conducted in the central-southwestern region of the Gulf of Mexico from February 19 to 10 March 2013. This study included the measurement of hydrographic and phytoplankton bio-optical parameters, and pigment samples were collected at two depth levels (10 and 50 m). Our results showed a warm and nutrient-depleted water column associated with low chlorophyll a (<1 mg Chla m−3) and average values of aph440 (0.01 ± 0.008, m−1) and ad350 (0.04 ± 0.02, m−1). In addition, nano-microphytoplankton abundance and pigments were analyzed using a light microscope and HPLC, respectively. Overall, the Gulf of Mexico exhibited oligotrophic characteristics, with Chla (0.17 ± 0.11 mg m−3) and NO3− (0.03 ± 0.001 µM), except at 50 m depth in some stations north of Yucatán and in Campeche Bay and at surface level off the Tamaulipas shelf. In these three regions, values of aph(440), ad(350), (Chla) and phytoplankton abundance (>12 × 103 cells L−1) were observed near river mouths and under seasonal oceanographic forcings, which increased the growth and diversity of phytoplankton. The most relevant pigments found were DVchla (0.06 ± 0.13 mg m−3), Chlb (0.16 ± 0.21 mg m−3), Zea (0.06 ± 0.03 mg m−3), and Hex-fuco (0.02 ± 0.02 mg m−3); these are associated with the presence of Prochlorococcus, chlorophytes, Synechococcus, prymnesiophytes, and diatoms. Through the bio-optical variability, we determined the ecological geography of phytoplankton in four different spectral shapes, where M1 and M2 represent the group of cyanobacteria (Prochlorococcus and Synechococcus) and M3 and M4 represent a mixture of diatoms, dinoflagellates, and chlorophytes. In conclusion, we consider that oceanographic processes such as cyclonic and anticyclonic structures and permanent rivers determine the favorable changes in phytoplankton (>nutrients, Chla, aph440) and an increment in the number of phytoplankton spectral shapes).